Strategi Guru dalam Membina Akhlakul Karimah Siswa Madrasah Ibtidaiyah - Rohana Sufia; Riska Rahayu; Tuti Marlina; Risma Firdia Diana (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2023)
The aims of this study is to provide an explanation of the teacher's strategy in fostering the morals of Madrasah Ibtidaiyah (MI) students. This study uses a type of qualitative research with the intention to understand the phenomenon of the things experienced by research subjects in a descriptive way. The research was carried out with the stages of preparation, implementation, and completion. The research subjects were teachers of the Akidah Akhlak subject, students, and parents of class 5A MI Al Fithrah Surabaya. Data collection techniques using observation, in-depth interviews, and documentation. Data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study revealed that the strategy used by Akidah Akhlak teachers in fostering akhlakul karimah class 5A students through the 8C program at MI Al Fithrah Surabaya. This program is very helpful in building children's character so that akhlakul karimah can be formed through habituation. The teacher's obstacle in implementing this strategy is the difficulty of directly monitoring the development and evaluation of students. Constraints experienced by students, namely the limitations of the learning process directly with the teacher and the lack of support from parents at home. The solution to this obstacle includes actively involving parents in raising awareness, responsibility, and discipline in their children.